INCREASING KNOWLEDGE OF HEALTHY LIFE AND HEALTH PROTOCOL COVID-19 IN JEMBER DISTRICT - Dimas BC Wicaksono; Adistha Eka Noveyani; Yunus Ariyanto; Rosidah Fidiyaningrum (UNEJ e-Proceeding, 2022)
The World Health Organization estimates that the Covid-19 Pandemic will end in 2022. However, this won’t be easy to realize if every country is unprepared to deal with the spread of Covid-19, considering that new variants of Covid-19 are starting to emerge. Therefore, applying health protocols and living a healthy life should not be reduced. Although the government has been intensively disseminating the Covid-19 vaccine and implementing health protocols, many Indonesians are still reluctant to comply. This Community Service activity was carried out in Karangrejo Village, RT 01/RW04, Sumbersari District, Jember Regency. The results of the problem diagnosis found that residents still did not understand how to live healthy during a pandemic and apply the correct health protocol. There are three activities in this community service, namely ADUHAI Education, GETAS Education, and the distribution of educational posters, masks, and educational banners. The result of this activity is that there is an increase in participants' knowledge from 73.31% (pre-test) to 97.48% (post-test) in the ADUHAI Education program and from 79.92% (pre-test) to 92.72% (post-test) on the GETAS Education program. Furthermore, the community is expected to practice independently in implementing healthy living recommendations and sustainably obeying health protocols. Keywords: education; health protocols; healthy living; covid-19